2021
DOI: 10.5093/apj2021a21
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, Reparation, and Quality of Life in Victims of Armed Conflict after Peace Agreements

Abstract: Quality of life has a global effect on society as a whole. The pragmatic study of quality of life allows to improve the conditions of mental health in a society, especially in those that are in a process of social, political, technological, and economic transformation (Cáliz et al., 2013). As Castañeda (2017) indicated, quality of life determines the level of mental health of a group through the evaluation of its impact Anuario de Psicología Jurídica (2021) xx xx-xx h t t p s : / / j o u r n a l s. c o p m a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Borine et al [ 47 ] and Tenais and Ribeiro [ 29 ] found similar results, caused by the lockdown measures enacted in Portugal. In addition, Simancas-Fernández et al [ 36 ], when assessing victims of the armed conflict, identified that the environmental domain was the most affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borine et al [ 47 ] and Tenais and Ribeiro [ 29 ] found similar results, caused by the lockdown measures enacted in Portugal. In addition, Simancas-Fernández et al [ 36 ], when assessing victims of the armed conflict, identified that the environmental domain was the most affected.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that different factors influence the QoL of victims of an armed conflict, including sociodemographic, social, and psychological characteristics. In 2019, in Colombia, Simancas-Fernández et al [ 36 ] assessed QoL in the victims of armed conflicts and identified that the environmental domain was the most affected due to disadvantages related to physical, health, and social care resources. Campo-Arias et al [ 37 ] conducted a systematic review of 13 studies that assessed the mental health of victims of armed conflicts and found that the prevalence of mental disorders was between 1.5 and 32.9%.…”
Section: Introductionmentioning
confidence: 99%
“…Las cifras de TEPT tienden a aumentar en contextos de guerra por los efectos que genera la presencia de grupos armados al margen de la ley, pues existe hasta 10 veces más de posibilidad de experimentar situaciones traumáticas que afectan el equilibrio psicológico de los individuos (Gómez-Restrepo et al, 2016;OMS, 2018). Se reconoce también que los síntomas de TEPT pueden presentar diferencias estadísticamente significativas en función del género (Manzanero et al, 2021) y de otras variables sociodemográficas como la edad, el nivel de ingresos, la educación o el trabajo (Simancas-Fernández et al, 2022). En Colombia, hay aproximadamente 8.9 millones de personas reconocidas como víctimas del conflicto armado (Red Nacional de Información, 2020).…”
Section: Anuario De Psicología Jurídica 2024unclassified
“…Sin duda el desplazamiento y los múltiples traumas que puede acarrear este evento generan efectos de largo alcance en múltiples niveles (Ramos-Vidal, 2018), afectando a la calidad de vida de los sobrevivientes, incluso después de lograr la firma de los acuerdos de paz (Simancas-Fernández et al, 2022). Por todo lo anterior este estudio se planteó comparar el número de sucesos traumáticos experimentados, la presencia de síntomas de TEPT y el deterioro en el funcionamiento en víctimas de desplazamiento forzado en el marco del conflicto armado que cumplen los criterios diagnósticos de TEPT (muestra clínica) y aquellos que no los cumplen (muestra subclínica).…”
Section: Anuario De Psicología Jurídica 2024unclassified
“…More effective studies on the psychological impact of war will support the development of better strategies to improve the victims’ QoL. This is particularly relevant in victims of the armed conflict in Colombia ( Hewitt-Ramírez et al, 2020 ) where low-to-medium QoL values have been reported ( Simancas-Fernández et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%